Awareness of the Existence of Leishmaniasis as Protozoan Zoonosis in Indonesia - Fitrine Ekawasti; E Martindah (Indonesian Center for Animal Research and Development, 2020)
Leishmaniasis is a zoonosis, neglected and poorly reported disease, caused by the protozoan Leishmania spp, genus Leishmania, transmitted through several vector species including the sand fly (gnat) genus Phlebotomus. This disease has complex ecology and epidemiology. This paper presents about Leishmaniasis disease from epidemiological aspects and risk factors; parasites, vectors and reservoirs; diseases transmission and control. Leishmania spp. is an obligate intramacrophage protozoan, characterized by its kinetoplast, a unique form of mitochondrial DNA. Clinical manifestations of Leishmaniasis depend on interactions between the characteristics of Leishmania species and the human host immune response, resulting in a diseases spectrum ranging from local lesions on the skin to diffuse involvement of the reticuloendothelial system. There are four forms of Leishmaniasis in humans with various clinical manifestations, namely visceral Leishmaniasis (VL), also known as kala-azar (KA), Cutaneous Leishmaniasis (CL), Mucocutaneous Leishmaniasis (MCL) and Diffuse Cutaneous Leshmaniasis (DCL). Leishmaniasis caused by Leismania infantum is the most dangerous disease, but is never found in Indonesia. Leishmaniasis needs to be aware in Indonesia as tropical country that is suitable for the habitat of sand flies (Phlebotomus). The best method for controlling this disease is effective vector control and reduced contact between humans and vectors.